A Newly Observed Mutation of the ABCA3 Gene Causing Lethal Respiratory Failure of a Full-Term Newborn: A Case Report - Jouza, Martin; Jimramovsky, Tomas; Sloukova, Eva; Pecl, Jakub; Seehofnerova, Anna; Jezova, Marta; Urik, Milan; Kunovsky, Lumir; Slaba, Katerina; Stourac, Petr; Klincova, Martina; Hubacek, Jaroslav A.; et al. (Frontiers in Genetics, 2020)
Respiratory distress syndrome caused by a secondary surfactant deficiency is one of the most common diagnoses requiring admission to the Neonatal Intensive Care Unit. We illustrate the case of a term female newborn without prenatal and peripartal risks. There had been significant signs of respiratory distress 4 h after delivery. The condition gradually worsened to the point of needing oscillatory ventilation. The most common infectious and noninfectious causes were excluded. Considering the course of illness, a congenital surfactant deficiency was suspected. There nevertheless was no significant improvement after administration of surfactant. Following a short period of palliative care, the child died at 34 days of age due to respiratory failure. DNA diagnostics revealed compound heterozygosity of ABCA3 functional mutations leading to the p.Pro147Leu and p.Pro246Leu exchanges. The second identified mutation of ABCA3 c.737C>T had not to date been described in connection with primary surfactant deficiency.